1990
DOI: 10.1029/jd095id04p03579
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of NO2 measurement techniques

Abstract: An intercomparison was made near Niwot Ridge, Colorado, of three different instruments for measuring NO2 at low concentrations in ambient air: (1) the photolysis/chemiluminescence (PC) instrument, (2) the tunable diode laser absorption spectrometer (TDLAS), and (3) the Luminox instrument. Calibrated mixtures of NO2 in air and NO2 with possible interferants (HNO3, peroxyacetyl nitrate (PAN), H2O2, n‐propyl nitrate, and O3) were provided in simultaneous tests. In addition, ambient air measurements were made usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(67 citation statements)
references
References 22 publications
2
62
0
2
Order By: Relevance
“…2 or 3 whether the PAN decomposition occurs within the BLC exclusively or within the inlet of the system, as has been claimed previously (Fehsenfeld et al, 1987). Previous studies (Fehsenfeld et al, 1990;Ridley et al, 1988;Sadanaga et al, 2010) have also reported a small PAN interference with photolytic converters, while some have found the contribution to the NO 2 signal from PAN to be negligible (Ryerson et al, 2000). Others (Val Martin et al, 2008) acknowledge the possibility for interference and estimate a small (2 to 4 pptv) positive bias.…”
Section: Inlet Residence Time Effectsmentioning
confidence: 60%
“…2 or 3 whether the PAN decomposition occurs within the BLC exclusively or within the inlet of the system, as has been claimed previously (Fehsenfeld et al, 1987). Previous studies (Fehsenfeld et al, 1990;Ridley et al, 1988;Sadanaga et al, 2010) have also reported a small PAN interference with photolytic converters, while some have found the contribution to the NO 2 signal from PAN to be negligible (Ryerson et al, 2000). Others (Val Martin et al, 2008) acknowledge the possibility for interference and estimate a small (2 to 4 pptv) positive bias.…”
Section: Inlet Residence Time Effectsmentioning
confidence: 60%
“…Subtraction of a similar plot of the NO loss expected from the gas-phase NO + O 3 reaction alone indicates the effect of wall reactions. 14 In most sensitive NO chemiluminescence monitors, a prereaction chamber is used during monitoring to allow reaction of NO with O 3 prior to the reaction cell, leaving a background signal that is subtracted on subsequent measurement of NO. An estimate of the limit of detection (LOD) for a signal-to-noise ratio (SNR) of 2 is 10 pptv for a 1-sec integration time and total uncertainty of ±10% for concentrations well above the detection limit.…”
Section: Methods For Monitoring Nomentioning
confidence: 99%
“…Because the TDL provides near unambiguous detection of target gases, it has frequently been used as a reference method in field test comparisons. Examples of its use for NO 2 include a comparison with the LMA-3 luminolbased NO 2 monitor at a field monitoring site 46 and other pre-1991 research, 4 including an intercomparison of NO 2 measurement techniques by Fehsenfeld et al 14 Reid et al 47 indicate that this type of system can achieve sensitivities on the order of 100 pptv.…”
Section: Tdl Absorption Spectroscopy-middle Infraredmentioning
confidence: 99%
See 2 more Smart Citations